Retrospective study of neoplastic cytological diagnoses of dogs and cats in an animal pathology laboratory from 2010 to 2020 (Research, Society and Development, 2023)
Cytological examination is an important tool in the diagnosis of neoplasms in companion animals. The objective of the study was to determine the prevalence of neoplasms in dogs and cats, diagnosed through cytological examination by the Veterinary Pathology Sector (SPV) of the Faculty of Veterinary Medicine of Araçatuba-FMVA/UNESP, from January 2010 to December 2020 13,037 cytological samples were collected from 8,868 animals, 94.66% (8,395) dogs and 5.34% (473) cats. Females had a higher prevalence, with 61.61% (5,464); males, 37.67% (3,367) and 37 animals had no description of sex. 72 breeds of dogs and 7 of cats were registered. The average age of dogs was 85.36 months (7 years) and cats, 81.18 months (6 years). The most prevalent diagnoses were non-neoplastic processes, 48.42% (6,313/13,037), followed by neoplastic processes, 33.29% (4,341/13,037); inconclusive, 16.5% (2,151/13,037) and unchanged 1.77% (232/13,037). Epithelial neoplasms were the most diagnosed, with 55.63% (2,415/4,341), followed by round cell neoplasms, 24.85% (1,079/4,341), and mesenchymal neoplasms, 18.08% (785/4,341). In dogs, the anatomical location with the highest incidence of neoplastic lesions was the abdominal region; in cats, the head. The retrospective study showed the cytological diagnostic profile of the region of Araçatuba, São Paulo.